Lanthanum Chloride Sensitizes Cisplatin Resistance of Ovarian Cancer Cells via PI3K/Akt Pathway - Fang, Shanyu; Zhang, Ping; Chen, Xinping; Liu, Fujun; Wang, Fen (Frontiers in Medicine, 2021)
Our previous study manifested that Lanthanum chloride (LaCl3) can enhance the anticancer ability of cisplatin (DDP) in ovarian cancer cells. Here, ovarian cancer cells SKOV3 and SKOV3/DDP were subjected to DDP and LaCl3. Cell viability, apoptosis, DNA repair, and PI3K/Akt pathway were detected. LaCl3 induced more cell death and apoptosis caused by DDP in two cell lines, accompanied by upregulation of Bax and Cleaved caspase 3 proteins, and down-regulation of Bcl-2 protein. LaCl3 also could decrease RAD51 protein by inactivation of PI3K/Akt pathway. These data indicated that LaCl3 could be a potential drug to modulate DDP resistance by inactivating of PI3K/Akt pathway and attenuating DNA repair in ovarian cancer.